The state of well-being in South East Asia at the turn of the new millennium and a decade after - Asmah Ahmad (Faculty of Social Sciences and Humanities, UKM,Bangi, 2010)
Recent writings on the state of the world today are often laced with alarming notes on the impending doom of mankind. Such notes pertain, among others, to the increasing economic discrepancies between the rich and the poor, the rapid increase in population growth, the cumulative destruction of the natural habitat and the rapidly growing powers unleashed by modern science and technology. They all signify issues, problems and challenges that countries and nations inherit from the last millennium. While the Southeast Asian region is no exception to this rule of living, even in the early decade of the new millennium, the curious question is how exactly do Southeast Asian countries comparatively fare in this context? This paper attempts to give an initial and tentative picture of the state of well-being of the Southeast Asian nations by analysing four major indicators, namely, GDP, unemployment, health and literacy. Lack of comparable data notwithstanding, it was found that a decade into the new millennium the region’s patterns of disparities persisted with Singapore heading the wellbeing list followed by Brunei, Malaysia and the rest. In conclusion, the legacy of the last millennium endures.